HUBUNGAN DUKUNGAN SUAMI DENGAN PEMBERIAN ASI DI KELURAHAN LALANG WILAYAH KERJA PUSKESMAS DESA LALANG KECAMATAN MEDAN SUNGGAL - Selli Dosriani Sitopu (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2017)
Breast Milk (ASI) is the best nutrition for baby that function for growth and development especially baby brain development. In the first months after birth is a period of rapid baby growth therefore breastfeeding should be maximized. Breastfeeding will be achieved well if you get family support, especially husbands. This research is descriptive correlation with cross sectional approach. The population in the study were breastfeeding mothers who had infants aged 0-12 months as many as 320 people and samples of 48 people and sampling technique is simple random sampling. Analysis technique in this research by using chi-square test. The results showed that there was a relationship of husband support with breastfeeding with p = 0.013 (p <0.05) which means the greater the support of husbands the greater the willingness of mothers to breastfeed. It is hoped for the husband to provide support and breastfeeding mothers always pay attention to nutrition that can support milk production. For nurses to improve health promotion efforts in the form of counseling about the need for breastfeeding.